1993
DOI: 10.1007/bf00189888
|View full text |Cite
|
Sign up to set email alerts
|

A calibration technique for multiple-sensor hot-wire probes and its application to vorticity measurements in the wake of a circular cylinder

Abstract: A calibration technique for multiple-sensor hot-wire probes is presented. The technique, which requires minimal information about the probe geometry, is tested using a four-sensor and a twelve-sensor probe. Two data reduction algorithms are introduced. The first one assumes a uniform velocity over the probe sensingvolume and is applied to the four-sensor probe measurements. The second one assumes a uniform velocity gradient over the sensing volume of the probe. The procedure, when applied to the twelvesensor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 11 publications
2
21
1
Order By: Relevance
“…The rms values of z from the ''vorticity probe'' agree well with those from X-wires y3-y8, thus providing another internal consistency check of the data. The present measurement has been compared with that of Marasli et al 17 and also Mi and Antonia. 21 Marasli et al used a twelve sensor vorticity probe with a spatial resolution of about 2 mm, while Mi and Antonia used two X wires, which were separated by 1.2 mm.…”
Section: Root Mean Square Distribution and Spectramentioning
confidence: 91%
See 2 more Smart Citations
“…The rms values of z from the ''vorticity probe'' agree well with those from X-wires y3-y8, thus providing another internal consistency check of the data. The present measurement has been compared with that of Marasli et al 17 and also Mi and Antonia. 21 Marasli et al used a twelve sensor vorticity probe with a spatial resolution of about 2 mm, while Mi and Antonia used two X wires, which were separated by 1.2 mm.…”
Section: Root Mean Square Distribution and Spectramentioning
confidence: 91%
“…A tiny peak is also identifiable in E x at f s L/U 1 Ϸ0.93, but not in E y . Marasli et al 17 observed a peak at f s in their z spectrum in a circular cylinder wake at x/dϭ30 and Reϭ2000, but not in either x or y spectra. The present vorticity data were approximately deduced from velocity signals.…”
Section: Root Mean Square Distribution and Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…While these quantities are available in direct numerical simulations of turbulent flows (e.g., [17,29,30]), only a few measurements have been attempted (e.g., [7,20,34,35]; see also [35]). Such measurements are useful for testing intermittency models (e.g., [21 ]), examining the properties of helicity ( [25,37]) and the correlation between velocity and vorticity [32,34].…”
Section: Introductionmentioning
confidence: 99%
“…(4) - (6), (8), (19)). Marasli et al (1993) (4) employed the modified nine-sensor probe to measure all three components of the vorticity vector in a turbulent intermediate wake. Using a simpler configuration, Zhu and Antonia (1996) (5) used four cross-wires to measure simultaneously the three vorticity components in a turbulent far wake.…”
Section: Introductionmentioning
confidence: 99%